'From garage to global': the internet and international market growth, an SME perspective. (5th February 2008) - Mathews, Shane; Healy, Marilyn
The internet has the capability to generate international market expansion and future growth for firms, a concept known as internetalisation. However, it is yet to be determined how much or to what extent the internet influences internationalisation, and thus international market growth. Both international market penetration (capitalising on existing country markets) and international market development (capitalising on new country markets) are achievable goals for the internet-enlightened Small and Medium Enterprises (SMEs). The aim of this research is to explore the influence of the internet on international market penetration and development for SMEs in Australia. The internet has given SMEs the capabilities to become rapidly or even instantly international. That is, the acceleration of internationalisation due to the internet has changed the once slow and cumbersome process of international market expansion. Specifically, an evolved version of accelerated internationalisation that incorporates the enhanced virtual network capability for SMEs is a more precise theoretical explanation.